2016
DOI: 10.3389/fpsyg.2016.00008
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Stereotype Threat is Critical to Diversity and Inclusion in Organizational Psychology

Abstract: Recently researchers have debated the relevance of stereotype threat to the workplace. Critics have argued that stereotype threat is not relevant in high stakes testing such as in personnel selection. We and others argue that stereotype threat is highly relevant in personnel selection, but our review focused on underexplored areas including effects of stereotype threat beyond test performance and the application of brief, low-cost interventions in the workplace. Relevant to the workplace, stereotype threat can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 168 publications
0
55
0
3
Order By: Relevance
“…It has been shown, for instance, that even simply being reminded of one's membership in a group that traditionally underperforms in a particular area of competence leads to a series of negative outcomes. Over the past two decades, hundreds of studies have demonstrated that stereotype threat has a pervasive and negative effect on individual performance, attitudes, motivations, and well-being (Casad & Bryant, 2016). Studies on this topic have focused on threats related to different group membership-such as gender, race, and age-in diverse social contexts (Spencer, Logel, & Davies, 2016).…”
mentioning
confidence: 99%
“…It has been shown, for instance, that even simply being reminded of one's membership in a group that traditionally underperforms in a particular area of competence leads to a series of negative outcomes. Over the past two decades, hundreds of studies have demonstrated that stereotype threat has a pervasive and negative effect on individual performance, attitudes, motivations, and well-being (Casad & Bryant, 2016). Studies on this topic have focused on threats related to different group membership-such as gender, race, and age-in diverse social contexts (Spencer, Logel, & Davies, 2016).…”
mentioning
confidence: 99%
“…Stereotype threat has many consequences [38] which can directly impact performance at interview and career progression. Stereotype threat also manifests in the workplace and can lead to a cascade of processes including reduced engagement, reduced or changed career aspirations, higher stress, poorer performance and higher failure rates [39]. Failure can reinforce the stereotype threat [37] and ''could be interpreted as evidence of supporting the stereotype'' [40].…”
Section: The Impact Of Stereotypingmentioning
confidence: 99%
“…Increasing personnel diversity, actively identifying similarities amongst group members and actively promoting the value of difference to problem solving are interventions that can be adapted in the workplace to counteract stereotype threat [39]. When teams are made up of people from many demographic groups the 'otherness' of an individual is less apparent.…”
Section: The Countermeasurementioning
confidence: 99%
See 2 more Smart Citations